Key virulence factors responsible for differences in pathogenicity between clinically proven live-attenuated Japanese encephalitis vaccine SA14-14-2 and its pre-attenuated highly virulent parent SA14 - Song, Byung-Hak; Yun, Sang-Im; Goldhardt, Joseph L.; Kim, Jiyoun; Lee, Young-Min (PLoS pathogens, 2025)
Japanese encephalitis virus (JEV), a neuroinvasive and neurovirulent orthoflavivirus, can be prevented in humans with the SA 14 -14-2 vaccine, a live-attenuated version derived from the wild-type SA 14 strain. To determine the viral factors responsible for the differences in pathogenicity between SA 14 and SA 14 -14-2, we initially established a reverse genetics system that includes a pair of full-length infectious cDNAs for both strains. Using this cDNA pair, we then systematically exchanged genomic regions between SA 14 and SA 14 -14-2 to generate 20 chimeric viruses and evaluated their replication capability in cell culture and their pathogenic potential in mice. Our findings revealed the following: ( i ) The single envelope (E) protein of SA 14 -14-2, which contains nine mutations (eight in the ectodomain and one in the stem region), is both necessary and sufficient to render SA 14 non-neuroinvasive and non-neurovirulent. ( ii ) Conversely, the E protein of SA 14 alone is necessary for SA 14 -14-2 to become highly neurovirulent, but it is not sufficient to make it highly neuroinvasive. ( iii ) The limited neuroinvasiveness of an SA 14 -14-2 derivative that contains the E gene of SA 14 significantly increases (approaching that of the wild-type strain) when two viral nonstructural proteins are replaced by their counterparts from SA 14 : ( a ) NS1/1’, which has four mutations on the external surface of the core β-ladder domain; and ( b ) NS2A, which has two mutations in the N-terminal region, including two non-transmembrane α-helices. In line with their roles in viral pathogenicity, the E, NS1/1’, and NS2A genes all contribute to the enhanced spread of the virus in cell culture. Collectively, our data reveal for the first time that the E protein of JEV has a dual function: It is the master regulator of viral neurovirulence and also the primary initiator of viral neuroinvasion. After the initial E-mediated neuroinvasion, the NS1/1’ and NS2A proteins act as secondary promoters, further amplifying viral neuroinvasiveness.